Salinity tolerance of tomato fertigated with different K+/Ca2+ proportions in protected environment - Francisco de A. de Oliveira; Francisco I. G. Paiva; José F. de Medeiros; Mikhael R. de S. Melo; Mychelle K. T. de Oliveira; Ricardo C. P. da Silvas (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Adequate potassium and calcium nutrition is a strategy to reduce salt stress on tomatoes, as it reduces nutritional imbalance in plants. With the objective of evaluating tomato production using irrigation with saline waters and fertigation with different potassium-calcium proportions, an experiment was carried out in a protected environment in Mossoró, RN, Brazil. The experimental design used was randomized blocks, in a 5 x 4 factorial scheme, with four replicates. The treatments consisted of the combination of four electrical conductivity of nutrient solution (ECns) (1.75; 3.25; 4.75; and 6.25 dS m-1) combined with five ionic proportions (m/m) of potassium and calcium (F1 = 2.43:1; F2 = 2.03:1; F3 = 1.62:1; F4 = 1.30:1 and F5 = 1.08:1). The response variables were: number of fruits, mean fruit weight, fruit production per plant and relative yield. It was possible to identify satisfactory results of production when higher salinity was used. Fertigation with low K+/Ca2+ proportions intensifies the effect of salinity on tomato crop.